Occult hepatitis B virus infection: clinical implications in tuberculosis treatment. Issue 12 (13th September 2016) - Trigo, C.; do Brasil, P. E. A. A.; Costa, M. J. M.; de Castro, L.
Abstract : Summary: Occult hepatitis B virus infection (OBI) is characterized by the absence of HBsAg and persistence of the virus genome (HBV‐DNA) in liver tissue and/or blood. OBI has been reported in several clinical contexts. However, the clinical significance of OBI in tuberculosis (TB) treatment is unknown. We investigated the OBI prevalence and its impact on the risk of drug‐induced liver injury (DILI) during TB treatment. This was a prospective cohort study with one hundred patients who were treated for TB from 2008 to 2015. Laboratory, clinical and demographic data of TB patients were extracted from medical records. Based on HBV‐DNA testing of serum samples, an OBI prevalence of 12% was established; almost half of these patients had both anti‐HBc and anti‐HBs serological markers. Low CD4 + cell counts have been shown to be a risk factor for OBI among TB patients co‐infected with HIV ( P =.036). High DILI incidence was observed in this study. A multivariable Cox proportional hazard model was conducted and identified OBI (HR 2.98, 95% CI 1.30–6.86) as the strongest predictor for DILI when adjusted to CD4 + cell count (HR 0.38, 95% CI 0.17–0.90), ALT before TB treatment (HR 1.37, 95% CI 0.81–2.32) and TB extrapulmonary clinical form (HR 2.91, 95% CI 1.75–7.21). The main aim of this study was to highlight DILI as a clinical outcome during treatment of TB patients with OBI. Therefore, HBV‐DNA testing should be considered routinely in monitoring DILI, and also in other clinical implications associated with OBI, reduce morbidity and mortality.